Do psychosocial factors predict pain after participation in an ultramarathon race? - Rabbitte, Jessica (Department of Health and Rehabilitation Sciences, 2020)
BACKGROUND Participation in ultramarathon races is increasing globally. Although endurance running has numerous physical and psychological benefits, due to the excessive volume of training and the physical and emotional demands of completing an ultramarathon event, exercise-induced muscle damage and delayed-onset muscle soreness are common. Recovery is central to improving performance and is also a determining factor in return to training. Recovery requires both physical and psychological adaptation. However, there is limited research exploring the effect psychosocial factors play on pain recovery following competition, particularly in endurance runners. More specifically, the role fear avoidance beliefs, pain catastrophizing and self-efficacy play in pain recovery following an ultramarathon race. This information is important to contribute to the limited research on the association between psychosocial factors and recovery from pain in endurance runners. Additionally, this information may provide insight into pain recovery following the Comrades Marathon and reduce time away from running.